AVALIAÇÃO DA EFICIÊNCIA DA ESTRUTURA E DO FUNCIONAMENTO DO SISTEMA DE CONTROLE GERENCIAL COM O PERFORMANCE MANAGEMENT AND CONTROL (PMC) EM DUAS UNIVERSIDADES - Ivonez Xavier de Almeida; Evanilde Gollo Cordazzo; Rodney Wernke; Antonio Zanin (Revista Gestão Universitária na América Latina, 2018)
The objective of the study was to know the opinion of two course coordinators about the utilization of control systems (SCG) in the performance evaluation in two higher education institution. The methodology utilized was descriptive, quantitative and the survey based in a questionnaire, it was sent to 150 course coordinators of two higher education institutions, with the feedback of 57 answers (38%). In the data analysis was utilized a descriptive statistics and the entropy of information to verify the grading levels dispersion in associated answers. The results show the average of “3,1” in the first higher education institution and “3,78” in the second higher education institution and agreement between the PMC, showing that the respondents partially agree with the structure efficiency and performance evaluation in both universities. However, about the performance management system the results confirm divergences between the contexts in the two universities studied. About the evaluation process efficiency the responses showed medium dispersion in relation to the range of 16 questions in PMC, comparing to the earlier researches. It was concluded the need of strategic alignment improvement in this two institutions, once the respondents know the strategic planning, but there are important failures in the development and the control in your implementation.